Presence of microplastic particles increased abundance of pathogens and antimicrobial resistance genes in microbial communities from the Oder river water and sediment - P. Cholewińska; K. Wojnarowski; N. Szeligowska; P. Pokorny; W. Hussein; Y. Hasegawa; W. Dobicki; D. Palić (Scientific Reports)
Abstract High abundance of microplastic particles (MPs) in the water environment could be a factor in spreading of pathogens and antimicrobial resistance genes (AMR), especially antibiotic resistance genes (ARGs). The aim of our study was to assess changes in the microbial community developing on microplastic surfaces incubated in water from the Oder River—one of Central Europe’s major rivers, flowing through three countries (Czechia, Germany, and Poland)—whose diverse, 20,000-km2 catchment area (encompassing industrial, agricultural, and urban regions) ensures a relatively high abundance of microbial communities.Samples of water and sediment were taken from river in Wroclaw area. Then the water was poured into disinfected glass liquid containers and pre-drained sediment was added. Control samples of water and sediment were collected on day 0. Then microplastic particles were added (500 mg; ~ 1 mm). Subsequent sampling was performed after incubation on 7th and 14th day. From each group, samples of sediment and water were collected after the incubation period (n = 5/group), for extraction of microbial DNA and library preparation. Sequencing was performed, using MinION sequencer with 10.4.1 Flow cell. Galaxy Europe platform and R program (v 4.3.3), alpha diversity and PERMANOVA with Benjamini–Hochberg p-value correction for multiple comparisons were used. For identification of biomarker taxa being different between groups, ANCOMBC (Analysis of Compositions of Microbiomes with Bias Correction) was performed. Obtained results shown higher abundance of pathogenic bacteria such as Aeromonas salmonicida Vibrio spp., Escherichia coli or Salmonella after 7 days of incubation in water and sediment. Additionally, after 7 days of incubation numbers of ARGs was higher compared to control group.